Effect of acrylic fibres geometry on physical, mechanical and durability properties of cement mortars - Oliveira, Luiz Antonio Pereira de (2012)
This paper presents the results of an experimental investigation to verify the feasibility of using acrylic textile fibre to improve cement based mortars properties. The assessment of acrylic fibres influence on mortars properties was performed comparing the physical, mechanical and durability behaviour with mortars produced using glass and polypropylene fibres. The influence of the mixing procedures was also investigated. Effects of acrylic fibre aspect ratio (l/d) and volume fraction (Vf) on mortar bulk density, compressive strength, flexural strength, water absorption and plastic shrinkage were investigated. For this purpose, acrylic fibres having six different l/d ratios 93, 148, 222, 278, 444 and 833 were used and the volume percentage of fibres were added to mortar mixes was of 0.2%; 0.5% and 1.0%. The mortar plastic shrinkage was also studied on slabs casted with 0.5%, 0.2%, 0.1% and 0.05 % acrylic fibres volume. It was found that acrylic fibre reinforced mortars have physical, mechanical and durability related properties similar to the mortar reinforced with glass or polypropylene fibres. These results indicate that there is a potential technical feasibility of using this type of fibres in cementitious composites.